Eksplorasi Pengalaman Mindfulness dalam Kesehatan Mental: Studi Fenomenologi pada Usia Dewasa - Fendy Fendy; Budi Utomo; Suherman Suherman (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study aims to explore the subjective experiences of mindfulness practice and its contribution to the mental health of adults at Cetiya Dhamma Manggala. A qualitative method with a phenomenological approach using Interpretative Phenomenological Analysis (IPA) was employed. Data were collected through semi-structured interviews, observation, and documentation with six adult participants actively engaged in mindfulness practice. The findings reveal that mindfulness practice provides holistic benefits encompassing psychological aspects (improved emotional regulation and cognitive clarity), physical aspects (better sleep quality and pain management), and social aspects (interpersonal harmony). However, participants also face challenges such as digital distractions, social resistance, and difficulties maintaining consistent practice. This study concludes that mindfulness has been subjectively experienced as a transformative path toward self-awareness and mental well-being.